PENGARUH MINUMAN BEROKSIGEN TERHADAP NILAI FEV1, FVC,VO2MAX DAN FREKUENSI NAFAS DENGAN LATIHAN FISIK METODE QUEEN’S COLLAGE STEP TEST PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS TANJUNGPURA ANGKATAN 2010 - 2012 - Indra Wijaya; H. Abdul Salam; Arundina TT (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2014)
Background: These last few years, bottled oxygenated water can be found in the market. The ads are also put forward the advantages of these products continue to flood the public in various media. Consumers believe that by consuming these oxygenated water, it will increase the capacity of oxygen in the blood and strengthen the immune system. Objective: This study aimed to determine differences in the effect of oxygenated water compared to ordinary drinking water in the value of FEV1, FVC, VO2Max and respiratory rate in men aged 18-21 years after physical exercise. Methods: This study was a quasi experimental study with cross-over method of pre and post test. Data were collected from 36 subjects using a brief questionnaire and a test with the Queen’s College Step Test. Data were analyzed with T test. Results: There was no difference in the effect of oxygenated water than ordinary drinking water in the value of FEV1 (p = 0.631), FVC (p = 0,765), respiratory rate (p = 0.594) and VO2max (p = 0.723). Conclusions: There was no significant difference between oxygenated water and ordinary drinking water in the changes of FEV1 (p=0.631), FVC (p=0.765), respiratory rate (p=0.594) and VO2Max (p=0.723) after physical exercise in men aged 18-21 years with a mean value in each group were: oxygenated water group’s FEV1 = 3.313 L/minute; FVC = 3.624 L/minute; Respiratory Rate = 30.08 L/minute and VO2Max = 61.803 mL/minute/kgBW, ordonary drinking water’s group FEV1 = 3.256 L/minute; FVC = 3.656 L/minute; Respiratory Rate = 29.22 L/minute and VO2Max = 63.053 mL/minute/kgBW.